Urinary cotinine concentration as a biomarker of environmental exposure to Nicotine in Vietnam: Results from a Nationwide Survey in 2024 - Hai Thanh Le; Thuy Thi Thu Tran; Binh Thi Ta; Huyen Thi Nguyen; Van Thi Pham; Chinh Thuy Thi Phan; Son Duc Nguyen; Nhat Minh Tu; Quynh Thuy Nguyen; Bich Ngoc Nguyen; Son Van Nguyen (PLoS ONE, 2026)
Background Accurate sources on environmental nicotine exposure, such as biomarker data, remain insufficient in low- and middle-income countries. This study aimed to i) determine the optimal cut-off point of urinary cotinine that discriminates smokers from non-smokers, ii) estimate misclassification rate between self-reported smoking and urinary cotinine, and III) explore the distribution of tobacco smoke exposure levels using urinary cotinine concentrations among adults in Vietnam in 2024. Methods A cross-sectional study was conducted in 2024 across seven provinces representing Vietnam’s ecological regions. Using multi-level stratified random sampling techniques, 1,077 adults aged 18–60 were recruited. Demographic and behavioural data were obtained through structured interviews. Urinary cotinine to creatinine ratios (CCR) were measured using high-performance liquid chromatography-tandem mass spectrometry. The Youden J method was used to determine the optimal cut-off point of CCR. Statistical analyses were performed using SPSS 20.0. Results Self-reported results showed that 18.3% were active smokers, 33.4% were exposed to SHS at home, and 48.3% lived in a non-smoking household. The optimal CCR cut-off value of 20.947 µg/g can distinguish smokers and non-smokers with a sensitivity of 61.5%, specificity of 93.2%, 70.6% positive predictive value and 90% negative predictive value. Regional disparities and urinary cotinine among the non-smoking groups suggest potential environmental exposure to nicotine. Conclusion The CCR level of 20.947 µg/g indicated the optimal cut-off value to distinguish smokers and non-smokers. Vietnam was among countries with high levels of environmental nicotine exposure, with significant variation by sex, education, occupation, income, and region. Urinary cotinine is a reliable biomarker for nicotine exposure and should be integrated into routine surveillance. These findings support the need for stricter enforcement of smoke-free environments and interventions tailored to reduce involuntary tobacco exposure.